Eco‐friendly method for rearing sea cucumber (Apostichopus japonicus) larvae. (24th April 2022) - Ru, Xiaoshang; Feng, Qiming; Zhang, Shuangyan; Liu, Shilin; Zhang, Libin; Yang, Hongsheng
Abstract: Seed production plays an important role in aquaculture. The sea cucumber Apostichopus japonicus is an important marine aquaculture species in many Asian countries. By 2020, the annual total seed production of A. japonicus reached 551 billion individuals in China. However, the traditional method of culturing A. japonicus larvae is cost intensive and causes environmental pollution. In this study, we developed an eco‐friendly method for rearing sea cucumber larvae. We designed a cage system to provide a suitable living environment for larvae in open‐air outdoor ponds, and then, we identified 0.2 larvae per ml as the optimal stocking density for larval rearing. We also found that substrates made of oyster and scallop shells were optimal for larval settlement. A. japonicus larvae showed good survival, growth, development and settlement when cultured using this low‐cost and non‐polluting method. Our results can be applied to support sustainable development of the sea cucumber industry.